Early Pliocene (Zanclean) sea surface temperature for PlioMIP3 - Harry J. Dowsett; Kevin M. Foley (Global and Planetary Change, 2026)

Killer whales in the Gulf of Mexico and North Atlantic off the Southeastern United States - Kevin P. Barry; Keith D. Mullin; Katherine Maze-Foley; Lynsey A. Wilcox Talbot; Patricia E. Rosel; Melissa S. Soldevilla; Laura Aichinger Dias; M. Rafael Ramírez-León; Jenny A. Litz (Frontiers in Marine Science, 2024)
Killer whales occur in the Gulf of Mexico (GoMex) and the North Atlantic, including off the southeastern United States (SEUS). Data from cetacean surveys during 1990 – 2021 and other sources were combined to assess killer whale biology, including spatial and temporal distribution, social structure, genetics, morphology, acoustics, and predatory behavior. GoMex records occurred predominantly in oceanic waters (>200 m) during spring and summer. SEUS records occurred primarily in winter and spring off the North Carolina region along the shelf-edge and deeper waters, and off the east coast of Florida. Photo-identification analysis of GoMex killer whales resulted in 49 individuals sighted up to seven times with sighting histories up to 26 years, and social analysis provided evidence of long-term relationships up to 16 years. The GoMex genetic samples revealed two mtDNA haplotypes, one of which does not match any outside the GoMex. Most GoMex whales had wide non-faint saddle patches and many had cookiecutter shark scars while no scars were noted on SEUS whales. Three groups recorded in the GoMex made few calls, but a group harassing sperm whales produced many. Cetaceans and tuna are known prey in the GoMex and SEUS, respectively. Directed studies of killer whales in the GoMex areas would be difficult to implement as this species is very rare. It is therefore important to pursue ongoing efforts to collect behavioral, acoustic and any biological samples that will contribute to improve our understanding of the biology and ecology of killer whales in tropical and subtropical regions.

Geographic and taxonomic variation in adaptive capacity among mountain-dwelling small mammals: Implications for conservation status and actions - Erik A. Beever; Jennifer L. Wilkening; Peter D. Billman; Lindsey L. Thurman; Kristina A. Ernest; David H. Wright; Alisha M. Gill; April C. Craighead; Nolan A. Helmstetter; Leona K. Svancara; Meghan J. Camp; Sabuj Bhattacharyya; et al. (Biological Conservation, 2023)

Effects of DHA on Hippocampal Autophagy and Lysosome Function After Traumatic Brain Injury - Yan Yin; Eric Li; George Sun; Hong Q. Yan; Lesley M. Foley; Liwia A. Andrzejczuk; Insiya Y. Attarwala; T. Kevin Hitchens; Kirill Kiselyov; C. Edward Dixon; Dandan Sun (Molecular Neurobiology, 2018)

Quantitative Temporal Profiles of Penumbra and Infarction During Permanent Middle Cerebral Artery Occlusion in Rats - Lesley M. Foley; T. Kevin. Hitchens; Brent Barbe; Feng Zhang; Chien Ho; Gutti R. Rao; Edwin M. Nemoto (Translational Stroke Research, 2010)